2023
DOI: 10.5114/reum/170845
|View full text |Cite
|
Sign up to set email alerts
|

The dichotomy of glucocorticosteroid treatment in immuneinflammatory rheumatic diseases: an evidence-based perspective and insights from clinical practice

Elvis Hysa,
Tamara Vojinovic,
Emanuele Gotelli
et al.

Abstract: ObjectivesGlucocorticosteroids (GCs) are the most used anti-inflammatory and immunosuppressive drugs due to their effectiveness in managing pain and disease modification in many immune-inflammatory rheumatic diseases (IRDs). However, their use is limited because of adverse effects (AEs).Material and methodsThe authors analyzed recent studies, including randomized controlled trials (RCTs), observational, translational studies and systematic reviews, providing an in-depth viewpoint on the benefits and drawbacks … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 99 publications
0
2
0
Order By: Relevance
“…On the other hand, GC are well known to induce a series of adverse events like infections, hypertension, diabetes mellitus, osteoporosis and fractures, gastrointestinal bleeding, glaucoma, and cataracts [ 51 ], which should be taken into account, especially in frail patients. One of the earliest and most cited observational studies that evaluated the rate of glucocorticoid-related adverse events [ 52 ] in GCA patients identified that 86% of patients had at least one adverse event, while two or more events occurred in 58% of patients, with the most frequent ones being cataracts, fragility fractures, and infections.…”
Section: Treatment Options In Gcamentioning
confidence: 99%
“…On the other hand, GC are well known to induce a series of adverse events like infections, hypertension, diabetes mellitus, osteoporosis and fractures, gastrointestinal bleeding, glaucoma, and cataracts [ 51 ], which should be taken into account, especially in frail patients. One of the earliest and most cited observational studies that evaluated the rate of glucocorticoid-related adverse events [ 52 ] in GCA patients identified that 86% of patients had at least one adverse event, while two or more events occurred in 58% of patients, with the most frequent ones being cataracts, fragility fractures, and infections.…”
Section: Treatment Options In Gcamentioning
confidence: 99%
“…The steroid group plays a structural role in cell membranes and contributes to physiological functions as a regulator of several important metabolic pathways as secondary messengers and hormones. For example, cortisol and synthetic cortisol-like compounds, termed as corticosteroids, help regulate blood pressure, immune function, and anti-inflammatory processes [ 2 , 3 ]. Moreover, phytosterols and phytostanols (e.g., β-sitosterol, campesterol, sitostanol, campestanol, and saringosterol) have been reported to exert biological effects, including lowering blood low-density lipoprotein cholesterol (LDL-C) levels, improving cognition function, and alleviating the pathology of Alzheimer’s disease [ 4 , 5 , 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%